Emergency Remote-Learning in Applying Project-based Learning in Translation Course to Improve Translation Quality and Students’ Creativity - Yuliasri, Issy; Kalisa, Pasca; Farida, Alief Noor; Suprapti, Sri (Universitas Negeri Semarang, 2023)
This research aims to investigate the use of project-based learning in translation courses, assess student responses to this approach, assess student knowledge and skills in translation techniques, and analyze the quality of student translation results using a project-based approach. This research uses a qualitative approach with exploratory and explanatory case study methods. The location of this research is at Universitas Negeri Semarang, with the focus on the English Language Education Study Program. Participants in this research consisted of 3 lecturers who taught the English-Indonesian Translation course in the 2021-2022 Even Semester, as well as around 150 students who took the course. Data collection was collected through interviews, observations, Forum Group Discussion (FGD), document analysis, as well as using questionnaires and documentation to measure student translation results. The research results show that project-based learning has succeeded in improving the quality of learning and student creativity in translating a text. Apart from that, students also showed a positive response to the application of the project-based learning model in the translation class.